Basic Amplifier Calculations - Kerekare, Bhagyalakshmi (McGraw-Hill's AccessEngineering., 2022)
This Excel workbook contains four worksheets. The first worksheet covers the amplifier basics such as calculation of voltage, current or power amplification, output voltage, noise factor and noise power. The second worksheet covers the calculations for Single stage BJT amplifier like input/output resistance, current gain, voltage gain and power gain for common base, common emitter and common collector amplifiers. The third worksheet covers the calculations of power gain, bandwidth, efficiency and slew rate for RC coupled audio amplifiers. The fourth worksheet covers calculations for operational amplifiers including calculation of closed loop gain, output voltage, and differential and common mode input signal of inverting and non-inverting amplifiers.